Systematic Review: Peran Sel, Jaringan, dan Kolagen dalam Penyembuhan Perforasi Membran Timpani - Antonius Christanto; Risya Cilmiaty; Made Setiamika; Ratih Dewi Yudhani; Paramasari Dirgahayu (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Tympanic membrane perforation is a significant clinical concern that can lead to hearing impairment and recurrent ear infections. This study aims to review the roles of Interleukin-1 beta (IL-1β), Fibroblast Growth Factor (FGF), fibroblasts, keratinocytes, granulation tissue, and collagen density during the wound-healing phases of the tympanic membrane.A Systematic Journal Review was conducted by analyzing studies retrieved from PubMed, Scopus, ScienceDirect, and Google Scholar databases published between 2020 and 2025. Of the 400 records screened,, 10 studies met the inclusion criteria. The findings revealed that IL-1β plays a key role in the inflammatory phase by modulating immune responses and recruiting healing cells. FGF stimulates fibroblast and keratinocyte proliferation, which are essential for extracellular matrix (ECM) remodeling and re-epithelialization. Moreover, granulation tissue formation and collagen deposition are critical determinants of structural integrity and healing quality. Overall, tympanic membrane repair requires synergistic interactions among molecular mediators, cellular components, and biomaterial support to optimize tissue regeneration. These findings provide a scientific basis for developing more effective regenerative and tissue-engineering strategies for middle ear therapy.